Decompensated alcoholic liver disease and birth weight. (13th March 2011) - Ali, A; Jones, J; Bradley, M P; Davies, R; Beck, R J; Gleeson, D
Abstract : Introduction: Only a minority of heavy drinkers develop serious alcoholic liver disease (ALD). Low birth weight has been associated with a several adult-onset diseases such as ischemic heart disease, hypertension and type 2 diabetes.1 Its association with ALD is not established. Using case-control strategy the authors aim to assess the associations between decompensated ALD and birth weight, prematurity and maternal smoking during pregnancy. Methods: The authors recruited two cohorts of heavy drinkers (≥60 U/week (men) and ≥40 U/week (women) for ≥5 years). Cases (n=215, 136 men, age (mean±SD) 46±9 years) had decompensated ALD (Child's grade B or C). Controls (n=163, 126 men, age 47±10 years) had no clinical evidence of liver disease, persistently normal serum bilirubin, albumin and prothrombin time and ultrasound showing normal or echo-bright texture and no other abnormality. Data were collected regarding subjects' birth weight, gestational age (GA) at birth (n=200 for cases, 148 for controls), and mother's smoking status during pregnancy (recalled by subjects, following discussion with mother when possible) (n=148 cases, 109 controls). Birth weight was classified as very low (<1.5 kg), low (1.5–2.5 kg), normal (2.5–4 kg) and high (>4 kg). Comparison between groups was by Student t and χ 2 tests. Recalled birth weights were also compared with actual birth weights in Sheffield hospital records, when these were available (22 cases, 13 controls) and close correlations were observed (r=0.80 for cases and 0.76 for controls; p<0.001 and 0.002). Results: See table 1 . There were no differences in birth weight or prevalence of low birth weight between males and females or between cases and controls when analysis was confined to males or to females. Conclusion: In this case-control study, the authors found no association between presence of ALD in heavy drinkers and either low birth weight or prematurity.